Fever range whole body hyperthermia for re-irradiation of head and neck squamous cell carcinomas: Final results of a prospective study. (May 2021) - Zschaeck, Sebastian; Weingärtner, Julian; Ghadjar, Pirus; Wust, Peter; Mehrhof, Felix; Kalinauskaite, Goda; Ehrhardt, Vincent H.; Hartmann, Vivian; Tinhofer, Ingeborg; Heiland, Max; Coordes, Annekatrin; Kofla, Grzegorz; et al.
Highlights: Fever range whole body hyperthermia improved oxygenation in preclinical models. This trial to used this method concurrent to re-irradiation of head and neck cancer. The primary aim of the trial was feasibility and was not met according to presets. There was no increase of toxicity by hyperthermia. Exploratory analyses showed potential to improve local control and quality of life. Abstract: Objectives: Fever-range whole body hyperthermia (FRWBH) has been shown to improve tumor oxygenation in vivo . A prospective pilot study addressed the question if addition of FRWBH to re-irradiation is feasible in recurrent head and neck squamous cell carcinomas (HNSCC) with unfavorable prognostic features. Materials and methods: The study completed accrual with the recruitment of ten patients between April 2018 and March 2020. Re-irradiation was administered using volumetric arc hyperfractionated radiotherapy with bi-daily 1.2 Gray (Gy) single fractions and a total dose of 66 Gy to all macroscopic tumor lesions. Concomitant chemotherapy consisted mostly of cisplatin (7 patients). FRWBH was scheduled weekly during re-irradiation. The study was registered in the clinicaltrials.gov database (NCT03547388). Results: Only five patients received all cycles of FRWBH. Poor patient compliance, active infections during treatment and study restrictions due to the Covid-19 pandemic were the main reasons for omitting FRWBH. No increase of acute toxicity was observed by FRWBH. Exploratory evaluation of outcome data suggests that FRWBH treatment according to protocol does not seem to have a detrimental effect on tumor control or survival and might even increase treatment efficacy. Conclusion: FRWBH is difficult to apply concomitant to re-irradiation in HNSCC. No excess toxicity was observed in patients receiving FRWBH and exploratory analyses suggest potential anti-tumor activity and decreased patient-reported depression scores after FRWBH.